Factors that influence customer buying decision towards Prudential Life Insurance / Muhammad Akhmal Mohamed Aris - Mohamed Aris, Muhammad Akhmal (Faculty of Business and Management, 2014)
Insurance is a promise of compensation for specific potential future losses in exchange for a periodic payment. Insurance is designed to protect the financial well-being of an individual, company or other entity in the case of unexpected loss. Some forms of insurance are required by law, while others are optional. Agreeing to the terms of an insurance policy creates a contract between the insured and the insurer. In exchange for payments from the insured (called premiums), the insurer agrees to pay the policy holder a sum of money upon the occurrence of a specific event. In most cases, the policy holder pays part of the loss (called the deductible), and the insurer pays the rest. Examples include car insurance, health insurance, disability insurance, life insurance, and business insurance. Life insurance can be defined as a protection against the loss of income that would result if the insured passed away. The named beneficiary receives the proceeds and is thereby safeguarded from the financial impact of the death of the insured. The goal of life insurance is to provide a measure of financial security for our family after we die. So, before purchasing a life insurance policy, we should consider our financial situation and the standard of living we want to maintain for our dependents or survivors. For example, who will be responsible for our funeral costs and final medical bills? Would our family have to relocate? Will there be adequate funds for future or ongoing expenses such as daycares, mortgage payments and college? It is prudent to re-evaluate our life insurance policies annually or when we experience a major life event like marriage, divorce, the birth or adoption of a child, or purchase of a major item such as a house or business. Assurance relates to the ability and skills of an employee to gain the trust of the customers, which is required to maintain a good customer contact through the creation and provision of good quality service (Bitner et al. 1990); and to build trust and customer satisfaction (Ahearne et al. 2007). Commitment as trust is one of the important thing as it also useful in measuring the likelihood of customer loyalty (Ndubisi and Wah, 2005:545). Most of the agent did not get the customer commitment in doing this Life Insurance. They must commit themselves to making it work. During the commitment stage of relationship marketing the parties reach a mature, stable period where the parties share the benefits of the relationship (Sauers, 2008:13). On the other hand, the agency must know how to overcome these issues before the agency falls. As agents, they should create a good relationship with the people surrounding and no cheating so that the people can trust them. Assurance of the straight-through administrative processing and transaction solutions for employers, intermediaries and retail customers enhances the service delivery of life insurance providers; and increases customer satisfaction since benefits are shared between different stakeholders, which contribute to positive growth in the social insurance market (Clark 2013). Mengi (2009) finds that assurance is important in the consumers’ utilization of the service. Therefore, it is crucial for service providers to provide quality assurance (Jones 1986).